On assessing the viral safety of individual units of the substance "Human plasma for fractionation" by nucleic acid amplification - E. V. Elbert; V. V. Nozhko; R. A. Volkova; A. A. Movsesyants; V. A. Merkulov; V. V. Kosenko (Биопрепараты: Профилактика, диагностика, лечение)
Scientific relevance. The absence of blood-borne viruses in human plasma-derived medicinal products must be ensured by the control of raw materials and the manufacturing process.Aim. This study aimed to analyse system suitability criteria for analytical procedures to assess the viral safety of individual units of the substance "Human plasma for fractionation" in terms of the content of nucleic acids of blood-borne viruses, considering the requirements of the European Pharmacopoeia.Materials and methods. The authors analysed individual units of the substance "Human plasma for fractionation" (hereinafter, plasma). The study used the International Standards (ISs) for human immunodeficiency virus RNA, hepatitis A virus (HAV) RNA, hepatitis C virus (HCV) RNA, hepatitis B virus (HBV) DNA, and parvovirus B19 DNA, as well as nucleic acid detection kits for these viruses based on polymerase chain reaction (PCR).Results. HCV RNA was not detected in any of the eight plasma samples studied, and parvovirus B19  DNA was detected in one of the samples at a concentration not exceeding 104  IU/mL.  Three tests with the corresponding ISs showed that the studied reagent kits detected HCV RNA at a concentration of 102 IU/mL and parvovirus B19 DNA (M1 genotype) at a concentration of  104 IU/mL. In additional tests that were conducted in two samples considering the requirements of the European Pharmacopoeia for the detection of HCV RNA and parvovirus B19 DNA, a new batch of reagent kit I detected the HCV RNA IS at a concentration of 102 IU/mL only in one of three replicates, which did not correspond to the claimed sensitivity of the reagent kit. HCV  RNA was not detected in either replicate in one of two plasma samples spiked with the HCV RNA IS at concentrations of 102 and 103 IU/mL, possibly because of plasma inhibitory properties. The sensitivity of the reagent kits to parvovirus B19 DNA corresponded to the label claims; the study did not show any inhibitory properties of the plasma samples.Conclusions. Polymerase chain reaction testing of the viral safety of plasma intended for manufacturing medicinal products should include control samples calibrated in IU/mL. Further research and appropriate pharmacopoeial reference materials are needed to set system suitability criteria for analytical procedures using such control samples.